Alteration of Anticancer and Protein-Binding Properties of Gold(I) Alkynyl by Phenolic Schiff Bases Moieties - Bandar A. Babgi; Jalal Alsayari; Hana M. Alenezi; Magda H. Abdellatif; Naser E. Eltayeb; Abdul-Hamid M. Emwas; Mariusz Jaremko; Mostafa A. Hussien (MDPI AG, 2021)
A set of five gold complexes with the general formula Au(PR3)(C≡C-C6H4-4-R') (R = PPh3, R' = -CHO (1), R = PCy3, R' = -CHO (2), R = PPh3, R' = -N=CH-C6H4-2-OH (3), R = PPh3, R' = -N=CH-C6H4-4-OH (4), R = PCy3, R' = -N=CH-C6H4-2-OH (5)) were synthesized and characterized by elemental analysis, 1H-NMR spectroscopy, 31P-NMR spectroscopy, and mass spectrometry. The structures of complexes 2 and 5 were determined by X-ray crystallography. The effects of the structural modifications on the protein binding affinities and anticancer activities of the five gold complexes were assessed. Fluorescence quenching experiments to assess binding to human serum albumin (HSA) revealed that the Schiff base complexes (3, 4, and 5) had binding constants that were superior to their parent aldehyde complexes and highlighted the position of the hydroxy group because complex 4 (4-hydroxy) had a binding constant 6400 times higher than complex 3 (2-hydroxy). The anticancer activities of the complexes against the OVCAR-3 (ovarian carcinoma) and HOP-62 (non-small-cell lung) cancer cell lines showed that the Schiff bases (3-5) were more cytotoxic than the aldehyde-containing complexes (1 and 2). Notably, compound 4 had cytotoxic activity comparable to that of cisplatin against OVCAR-3, demonstrating the significance of the para position for the hydroxy group. Molecular docking studies against the enzyme thioredoxin reductase (TrxR) and human serum albumin were conducted, with docking scores in good agreement with the experimental data. The current study highlights how small structural modifications can alter physiochemical and anticancer properties. Moreover, this simple design strategy using the aldehyde group can generate extensive opportunities to explore new gold(I)-based anticancer drugs via condensation, cyclization, or nucleophilic addition reactions of the aldehyde.